Computer programs for analysis of solar domestic hot water systems: RETScreen case study. (2015) - Altoé, Leandra; Filho, Delly Oliveira; Martinez, Francisco Javier Rey; Carlo, Joyce Correna; Monteiro, Paulo Marcos de Barros
No abstract available